Comparative Analysis of Career Adaptability among Working and Non-Working Students in the Philippines - Shaira Pingol; Kate Cheska Dasalla; Jaime Rica Diamzon; Ceanne Gayle Felizmena; Alhyana Jhay Hernandez; Jerald Vergara; Kimberly Ann Cantilero (Future Science / FSH-PH Publications, 2025)
In today’s fast-paced and competitive job market, the capacity to adapt to career changes and challenges is essential for long-term success. Transitioning from academia to a professional career can be challenging for learners. Career adaptability is a trait that students utilise to navigate uncertainty in the workplace. Although numerous studies compared working and non-working students, few have specifically examined their career adaptability in the local context. Most existing research centers on post-employment outcomes such as job satisfaction and career growth, with limited attention given to the demographics of currently enrolled university students. This comparative study explored the career adaptability of university students in the Philippines. Using the Career Adaptability Assessment Scale (CAAS), data were collected from both groups through an online questionnaire. An independent samples t-test was used to compare the means of career adaptability dimensions and overall career adaptability between working and non-working students. Results showed a significant difference in career confidence (p = 0.002, d = -0.44) and overall career adaptability (p = 0.04, d = -0.29) between the two groups, demonstrating higher levels in working students. Furthermore, no significant difference was observed in terms of career concern (p = 0.18), career control (p = 0.43), and career curiosity (p = 0.45). These findings suggest that while employment status is associated with differences in career adaptability and confidence among students, the practical effect size of this difference is limited. The findings identify potential areas for targeted institutional support for student career development.